Sustainable production strategies in agricultural transport: Balancing economic efficiency and environmental impact - Przemysław Niewiadomski; Agnieszka Merkisz-Guranowska (Journal of Sustainable Development of Transport and Logistics, 2024)
Purpose. This paper aims to present a sustainable production strategy for manufacturing parts and components for agricultural transport means, focusing on minimising production costs and post-production waste generation. Methodology. The research employs a case study approach, using participant observation and analysis of a manufacturing company's specific production process for an agricultural trailer floor panel. The authors propose a model for optimising raw material selection and utilising post-production waste to achieve economic and environmental savings. Results. The results demonstrate that by selecting the appropriate raw material dimensions and implementing a product diversification strategy to utilise post-production waste, the manufacturer can reduce material costs and environmental losses while generating additional revenue streams. Theoretical contribution. The study contributes to sustainable production management by proposing a practical strategy model that balances economic efficiency and environmental concerns in manufacturing agricultural transport components. The model emphasises the importance of raw material selection, waste minimisation, and product diversification to achieve sustainability goals. Practical implications. The findings provide valuable insights for manufacturers in the agricultural transport sector, highlighting the potential benefits of adopting sustainable production strategies. The proposed model can be implemented in practice to optimise resource utilisation, reduce waste generation, and improve overall economic and environmental performance.